Flexibility at the margin and labor market volatility in OECD countries - Héctor Sala; José Ignacio Silva; Manuel E. Toledo (Institute for the Study of Labor (IZA), 2008)
We study whether segmented labor markets with flexibility at the margin (e.g., just affecting fixed-term employees) can achieve similar volatility than fully deregulated labor markets. Flexibility at the margin produces a gap in separation costs among matched workers that cause fixed-term employment to be the main workforce adjustment device, which in turn increases de labor market volatility. This increased volatility is partially reverted when limitations in the duration and number of renewals of fixed-term contracts are introduced. Under this scenario, firms respond by reducing the intensity of job destruction since it becomes more difficult to avoid firing costs in permanents contracts. We present a matching model with temporary and permanent jobs where (i) the gap in firing costs and (ii) restrictions in the use of fixed-term contracts helps explain the similar volatility observed in many regulated OECD labor markets with flexibility at the margin vis-à-vis the fully deregulated ones.
Keywords: J23; 330; Flexibility at the margin; volatility; separation costs; matching model; Arbeitsmarktsegmentierung; Arbeitsmarktflexibilisierung; Volatilität; Theorie; OECD-Staaten